Computational Modelling of Glucose Uptake by SGLT1 and Apical GLUT2 in the Enterocyte - Afshar, Nima; Safaei, Soroush; Nickerson, David P.; Hunter, Peter J.; Suresh, Vinod (Frontiers in Physiology, 2021)
It has been suggested that glucose absorption in the small intestine depends on both constitutively expressed SGLT1 and translocated GLUT2 in the brush border membrane, especially in the presence of high levels of luminal glucose. Here, we present a computational model of non-isotonic glucose uptake by small intestinal epithelial cells. The model incorporates apical uptake via SGLT1 and GLUT2, basolateral efflux into blood via GLUT2 and cellular volume changes in response to non-isotonic conditions. Dependence of glucose absorption on luminal glucose, blood flow rate and inlet blood glucose concentration is studied. Uptake via apical GLUT2 is found to be sensitive to all these factors. Under a range of conditions the maximum apical GLUT2 flux is about half of the SGLT1 flux and is achieved at high luminal glucose (> 50 mM), high blood flow rates and low inlet blood concentrations. In contrast, SGLT1 flux is less sensitive to these factors. The model results indicate that translocation of GLUT2 from the basolateral to the apical membrane increases glucose uptake into the cell; however, the reduction of efflux capacity results in a decrease in net absorption. When luminal glucose concentration is less than 10 mM, apical GLUT2 serves as an efflux pathway for glucose to move from the blood to the lumen. Recruitment of GLUT2 from a cytosolic pool elicits 10-20% increase in absorption for luminal glucose levels in the 20-100 mM range. Increased SGLT1 activity also leads to a roughly 20% increase in absorption. Concomitant increase in blood supply results in a larger increase in absorption. Increases in apical glucose transporter activity help to minimise cell volume changes by reducing the osmotic gradient between the cell and the lumen.